Early Effects of Altered Gravity Environments on Plant Cell Growth and Cell Proliferation: Characterization of Morphofunctional Nucleolar Types in an Arabidopsis Cell Culture System - Manzano, Ana I.; Herranz, Raúl; Manzano, Aránzazu; van Loon, Jack J. W. A.; Medina, F. Javier (Frontiers in Astronomy and Space Sciences, 2016)
Changes in the cell growth rate of an in vitro cellular system in Arabidopsis thaliana induced by short exposure to an altered gravity environment have been estimated by a novel approach. The method consisted of defining three structural nucleolar types which are easy and reliable indicators of the ribosome biogenesis activity and, consequently, of protein biosynthesis, a parameter strictly correlated to cell growth in this cellular system. The relative abundance of each nucleolar type was statistically assessed in different conditions of gravity. Samples exposed to simulated microgravity for 200 min showed a significant decrease in nucleolar activity compared to 1g controls, whereas samples exposed to hypergravity (2g) for the same period showed nucleolar activity slightly increased. These effects could be considered as an early cellular response to the environmental alteration, given the short duration of the treatment. The functional significance of the structural data was validated by a combination of several different well-known parameters, using microscopical, flow cytometry, qPCR, and proteomic approaches, which showed that the decreased cell growth rate was decoupled from an increased cell proliferation rate under simulated microgravity, and the opposite trend was observed under hypergravity. Actually, not all parameters tested showed the same quantitative changes, indicating that the response to the environmental alteration is time-dependent. These results are in agreement with previous observations in root meristematic cells and they show the ability of plant cells to produce a response to gravity changes, independently of their integration into plant organs.